A Transfer of Modern Technologies from Universities to SMEs-Organisational — the Picture in Polish Media - Tomasz Hoffmann (Технологія і техніка друкарства, 2018)
A matter of scientific researches results’ commercialisation and technology transfer is an issue not fully explored yet in a Polish literature and practice, hence it seems that any actions undertaken by particular universities in this field will be based on experiences gained in a process of implementing new ideas. Undoubtedly, these experiences will be also gained in the way of appointing special purpose entities which will have a basic task of the commercialisation and technology transfer.